2010
DOI: 10.1038/emboj.2010.311
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between lysine methylation and Cdk phosphorylation in growth control by the retinoblastoma protein

Abstract: As a critical target for cyclin-dependent kinases (Cdks), the retinoblastoma tumour suppressor protein (pRb) controls early cell cycle progression. We report here a new type of regulation that influences Cdk recognition and phosphorylation of substrate proteins, mediated through the targeted methylation of a critical lysine residue in the Cdk substrate recognition site. In pRb, lysine (K) 810 represents the essential and conserved basic residue (SPXK) required for cyclin/Cdk recognition and phosphorylation. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(134 citation statements)
references
References 37 publications
4
130
0
Order By: Relevance
“…Meanwhile, the level of H3K9me3 was basically unchanged. Moreover, the H3K27me3 was present as a circular ring around the DAPI foci (Supplementary Figure S4), a phenomenon also reported by Carr et al 28 We then analyzed the distribution of JMJD3 upon the formation of SAHF, and interestingly, we detected the localization of JMJD3 to the cytoplasm (Figure 3b). In addition, the JMJD3 distribution was colocalized with the Golgi protein GM130 (Supplementary Figure S5).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Meanwhile, the level of H3K9me3 was basically unchanged. Moreover, the H3K27me3 was present as a circular ring around the DAPI foci (Supplementary Figure S4), a phenomenon also reported by Carr et al 28 We then analyzed the distribution of JMJD3 upon the formation of SAHF, and interestingly, we detected the localization of JMJD3 to the cytoplasm (Figure 3b). In addition, the JMJD3 distribution was colocalized with the Golgi protein GM130 (Supplementary Figure S5).…”
Section: Resultssupporting
confidence: 72%
“…Earlier studies have demonstrated that methylation at RB K810 by Set7/9 retains the hypophosphorylated state of RB and suppresses cellular growth in U2OS cells, 28 whereas the SMYD2-dependent methylation of RB K810 promotes cell cycle progression in SW780 and RT4 cells. 29 Apparently, our results are in favor of that described by Cho et al 29 that methylation of RB K810 promotes cell cycle progression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A large number of methyltransferases have been identified, which can loosely be divided into two subgroups; lysine methyltransferases, mostly belonging to the SET domain family (Martin and Zhang, 2005), and arginine methyltransferase, referred to as protein arginine dimethyltransferases (Bedford and Clarke, 2009). Very interestingly, pRb is methylated by the mono-methyltransferase Set7/9 at two distinct lysine residues within the C-terminal domain of pRb, K873 and K810 (Munro et al, 2010;Carr et al, 2011) (Figure 1). Methylation of pRb at K873 creates a binding site for the heterochromatin protein, HP1.…”
Section: Prb Methylationmentioning
confidence: 99%
“…K810 lies within a Cdk consensus motif and is flanked by S807 and S811, and methylation of K810 prevents phosphorylation of the juxtapositioned sites (Carr et al, 2011) (Figure 1). During the DNA damage response, pRb is predominantly hypophosphorylated (Knudsen et al, 2000).…”
Section: Prb Methylationmentioning
confidence: 99%